Allocation of food resource by experimentally evolved lines of developmental variants of Propylea dissecta: a food exploitation strategy. Issue 2 (19th April 2023) - Siddiqui, Arshi; Omkar,; Mishra, Geetanjali
Abstract: The effects of selection on developmental variants have not yet been rigorously investigated on variable prey quantities. We investigated the food exploitation strategy of first ( F 1 ) and fifteenth ( F 15 ) generation slow and fast developers of Propylea dissecta (Mulsant) in the presence of scarce and abundant quantities of pea aphid, Acyrthosiphon pisum (Harris), and its effect on adult body mass and reproductive attributes. Both selected slow developers and selected fast developers were higher in number than their counter unselected generation on scarce and abundant diets, respectively. Immature survivals of selected slow developers were depressed after the selection process while it was enhanced for selected fast developers on both diet regimes. On both diets, the total developmental duration was longer for selected slow developers and shorter for selected fast developers. Fecundity and percent egg viability were greater in selected fast developers with plentiful prey supply and lower in control slow developers with inadequate prey supply. More adult body mass was found for pre-selected slow developers than selected slow developers on a scarce diet but selected fast developers enhanced their body weight than unselected individuals of fast developers on an abundant diet. The present experimental evolution findings point to the presence and persistence of developmental variations with variability in their developmental and reproductive traits on allocating scarce and abundant prey supplies.